Unconjugated bilirubin elevation impairs the function and expression of breast cancer resistance protein (BCRP) at the blood-brain barrier in bile duct-ligated rats - Xu Ping; Ling Zhao-li; Zhang Ji; Li Ying; Shu Nan; Zhong Ze-yu; Chen Yang; Di Xin-yu; Wang Zhong-jian; Liu Li; Liu Xiao-dong (Acta Pharmacologica Sinica, 2017)
Aim: Liver failure is associated with dyshomeostasis of efflux transporters at the blood-brain barrier (BBB), which contributes to hepatic encephalopathy. In this study we examined whether breast cancer resistance protein (BCRP), a major efflux transporter at the BBB, was altered during liver failure in rats. Methods: Rats underwent bile duct ligation (BDL) surgery, and then were sacrificed after intravenous injection of prazosin on d3, d7 and d14. The brains and blood samples were collected. BCRP function at the BBB was assessed by the brain-to-plasma prazosin concentration ratio; Evans Blue extravasation in the brain tissues was used as an indicator of BBB integrity. The protein levels of BCRP in the brain tissues were detected. Human cerebral microvessel endothelial cells (HCMEC/D3) and Madin-Darby canine kidney cells expressing human BCRP (MDCK-BCRP) were tested in vitro. In addition, hyperbilirubinemia (HB) was induced in rats by intravenous injection of unconjugated bilirubin (UCB). Results: BDL rats exhibited progressive decline of liver function and HB from d3 to d14. In the brain tissues of BDL rats, both the function and protein levels of BCRP were progressively decreased, whereas the BBB integrity was intact. Furthermore, BDL rat serum significantly decreased BCRP function and protein levels in HCMEC/D3 cells. Among the abnormally altered components in BDL rat serum tested, UCB (10, 25 μmol/L) dose-dependently inhibit BCRP function and protein levels in HCMEC/D3 cells, whereas 3 bile acids (CDCA, UDCA and DCA) had no effect. Similar results were obtained in MDCK-BCRP cells and in the brains of HB rats. Correlation analysis revealed that UCB levels were negatively correlated with BCRP expression in the brain tissues of BDL rats and HB rats as well as in two types of cells tested in vitro. Conclusion: UCB elevation in BDL rats impairs the function and expression of BCRP at the BBB, thus contributing to hepatic encephalopathy.